Pull and Push Factors for Tourists to Choose Wellness Tourism in Bali Eling Spirit - I Gusti Agung Ngurah Wasudewa Wikananda; Putu Indah Budi Apsari; Made Indra Wijaya (Warmadewa University, 2024)
Wellness tourism is a tourist activity that has become popular in society nowadays as an alternative to carrying out non-pharmacological therapy to achieve body balance, mind, and spirit. Bali is a popular destination for wellness activities such as SPAs, yoga, and meditation. This research aims to analyze the pull and push factors influencing tourists’ choice of wellness tourism in Bali. This cross-sectional descriptive research uses yogists who come to Bali Eling Spirit as samples. The target population was all yogis in Bali Eling Spirit Yoga Centre. The sample was selected by consecutive sampling; all yogists were recruited as samples and met inclusion criteria. This research used a questionnaire method to collect data. The measuring indicators in this questionnaire use a Likert scale. This study adopted a questionnaire that existed in previous research. The location of this research was Gianyar Regency, namely Bali Eling Spirit. The results show that most samples were women who chose yogas as wellness tourism, and push and pull factors were in high classification. Yoga is the type of wellness that respondents most frequently practice. Respondents chose Yoga in Bali Eling Spirit because of its simple technique and cheap price. Pull and push factors for tourists choosing wellness tourism in Bali Eling Spirit receive high scores for healing, Bali's natural beauty, and various types of wellness. Further research must be conducted to apply this pull and push factor in other wellness types.